Successes in development of advanced acceleration methods (overview) - Onishchenko, I.N. (Вопросы атомной науки и техники, 2008)
The most recent results on laser and plasma accelerators are presented and discussed, along with the future developments and their impact on table-top accelerators and related applications, as well as the impact of particle acceleration using plasmas in the quest for the energy frontier. Ultra intense laser and particle beams are pushing particle acceleration using plasmas to regimes unconceivable just a few years ago: 1 GeV monoenergetic electron beams from a laser-plasma accelerator, energy doubling of the 42 GeV SLAC beam, controlled injection of monoenergetic relativistic electron beams, and quasi-monoenergetic MeV ion beams are just some of the groundbreaking experimental results in 2006. In the next couple of years, more exciting developments in laser and plasma accelerators are to be expected. New PW-range laser systems and R&D programs in this field are spreading all over the world, and large-scale numerical simulations are providing information with unprecedented details.